Women in rural development research and training programmes in Universiti Pertanian Malaysia - Mahfoz, Napsiah; Sulaiman, Husna (1988)
This paper discusses the roles of women in rural development and the programs of research and training in Universiti Pertanian Malaysia. Women form an important group of human resource, one of the major factors in shaping the social and economic development of a community. Rural women contribute significantly towards the socio-economic development of rural families and the community through their two major roles. Through their socially-ascribed family-management role, they create an environment conducive for healthy living and critical for developing productive members of society. Through their economic production activities, they help improve the economic well-being of rural families. Women's contribution to rural development is dependent on the availability of other, non-human resources and their knowledge, skills, attitude and ability to develop and utilise these resources. Research findings are useful in formulating policies and developing programmes for improving the status of rural women and their contribution towards deve1opment. Training programmesare equally important in enhancing women 's role in development. The Women's Studies Unit, Universiti Pertanian Malaysia conducts training programmes and collaborates with other agencies and organisations in our efforts to get women to participate more actively in the development process. These programmes include leadership courses and development of training packages and selfinstructional modules to help extension workers and women leaders educate rural women improve their life. These modules cover subject areas such as home management, health care, nutrition and consumer education. Efforts need to be continued to maximize the contribution of women in rural development. These include ensuring, through research and training programmes, that rural development programmes take into account women's needs and that rural women are equipped with toe necessary knowlege and skills to enable them to participate actively in the development process and consequently improve their socio-economic wellbeing.